Zinc Oxide-Based Q-Switched Erbium-Doped Fiber Laser - Aziz, N. A.; Abdul Latiff, Anas; Lokman, Muhammad Quisar; Hanafi, Effariza; Harun, Sulaiman Wadi (Institute Of Physics (IOP) Publishing, 2017)
We demonstrate a Q-switched erbium-doped fiber laser (EDFL) using a newly developed zinc oxide- (ZnO) based saturable absorber (SA). The SA is fabricated by embedding a prepared ZnO powder into a poly(vinyl alcohol) film. A small piece of the film is then sandwiched between two fiber ferrules and is incorporated in an EDFL cavity for generating a stable Q-switching pulse train. The EDFL operates at 1560.4nm with a pump power threshold of 11.8mW, a pulse repetition rate tunable from 22.79 to 61.43 kHz, and the smallest pulse width of 7.00